Effect of structured physical activity on prevention of serious fall injuries in adults aged 70-89: randomized clinical trial (LIFE Study). (3rd February 2016) - Gill, Thomas M; Pahor, Marco; Guralnik, Jack M; McDermott, Mary M; King, Abby C; Buford, Thomas W; Strotmeyer, Elsa S; Nelson, Miriam E; Sink, Kaycee M; Demons, Jamehl L; Kashaf, Susan S; Walkup, Michael P; et al.
Abstract : Objective To test whether a long term, structured physical activity program compared with a health education program reduces the risk of serious fall injuries among sedentary older people with functional limitations. Design Multicenter, single blinded randomized trial (Lifestyle Interventions and Independence for Elders (LIFE) study). Setting Eight centers across the United States, February 2010 to December 2011. Participants 1635 sedentary adults aged 70-89 years with functional limitations, defined as a short physical performance battery score ≤9, but who were able to walk 400 m. Interventions A permuted block algorithm stratified by field center and sex was used to allocate interventions. Participants were randomized to a structured, moderate intensity physical activity program (n=818) conducted in a center (twice a week) and at home (3-4 times a week) that included aerobic, strength, flexibility, and balance training activities, or to a health education program (n=817) consisting of workshops on topics relevant to older people and upper extremity stretching exercises. Main outcome measures Serious fall injuries, defined as a fall that resulted in a clinical, non-vertebral fracture or that led to a hospital admission for another serious injury, was a prespecified secondary outcome in the LIFE Study. Outcomes were assessed every six months for up to 42 months by staff masked to intervention assignment. All participants were included in the analysis. Results Over a median follow-up of 2.6 years, a serious fall injury was experienced by 75 (9.2%) participants in the physical activity group and 84 (10.3%) in the health education group (hazard ratio 0.90, 95% confidence interval 0.66 to 1.23; P=0.52). These results were consistent across several subgroups, including sex. However, in analyses that were not prespecified, sex specific differences were observed for rates of all serious fall injuries (rate ratio 0.54, 95% confidence interval 0.31 to 0.95 in men; 1.07, 0.75 to 1.53 in women; P = 0.043 for interaction), fall related fractures (0.47, 0.25 to 0.86 in men; 1.12, 0.77 to 1.64 in women; P = 0.017 for interaction), and fall related hospital admissions (0.41, 0.19 to 0.89 in men; 1.10, 0.65 to 1.88 in women; P=0.039 for interaction). Conclusions In this trial, which was underpowered to detect small, but possibly important reductions in serious fall injuries, a structured physical activity program compared with a health education program did not reduce the risk of serious fall injuries among sedentary older people with functional limitations. These null results were accompanied by suggestive evidence that the physical activity program may reduce the rate of fall related fractures and hospital admissions in men. Trial registration ClinicalsTrials.gov NCT01072500 .